PENGEMBANGAN STRATEGI IS/IT DALAM BERBAGAI BIDANG BISNIS: STATE OF THE ART (Jurnal Sistem Informasi dan Sains Teknologi, 2022)
ABSTRACTIS/IT strategy is one of the keys to a company's success in running a business. IS/IT is usually in line with existing business strategies. In the last few decades, many IS/IT models have been developed and implemented with the aim of improving business management by utilizing the latest technology. Motivated by the application of IS/IT in various business models, this paper aims to emphasize the importance of this strategy in business transformation. This paper contains an overview of the strategy and identification of IS/IT strategies that have been implemented in various business areas. This paper is expected to provide additional knowledge for researchers, communities and IS/IT practitioners in developing and implementing better IS/IT in the future. Keywords: IS/IT strategy, business strategy, management IT